2008
DOI: 10.1292/jvms.70.189
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Antigen Detection Kits for Diagnosis of Equine Influenza

Abstract: ABSTRACT. In this study, we evaluated whether five rapid antigen detection kits for human influenza could be used for the diagnosis of equine influenza (EI). Limiting dilution analyses showed that Directigen Flu A+B and ESPLINE INFLUENZA A&B-N had the highest sensitivities to equine-2 influenza viruses (EIVs) among the kits investigated. From the results of virus detection in nasal swabs taken from horses infected with EIV, these two kits could produce positive results in reasonable agreement with those obtain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
21
1
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 13 publications
(18 reference statements)
1
21
1
1
Order By: Relevance
“…The Directigen Flu A test was the least sensitive method for detection of EIV. In a similar study, Yamanaka et al (46) demonstrated that VI in embryonated eggs is more sensitive than the five rapid antigen detection kits evaluated. Furthermore, analysis of nasal swabs from a limited number of experimentally inoculated horses also showed that VI by egg inoculation and the standard RT-PCR had comparable sensitivities in detecting EIV (34).…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…The Directigen Flu A test was the least sensitive method for detection of EIV. In a similar study, Yamanaka et al (46) demonstrated that VI in embryonated eggs is more sensitive than the five rapid antigen detection kits evaluated. Furthermore, analysis of nasal swabs from a limited number of experimentally inoculated horses also showed that VI by egg inoculation and the standard RT-PCR had comparable sensitivities in detecting EIV (34).…”
Section: Discussionmentioning
confidence: 94%
“…These methods are time-consuming and cumbersome. In the past decade, antigen detection immunoassays, such as the Directigen Flu A test kit (Becton-Dickinson, Sparks, MD) and nucleic acid amplification-based assays (standard reverse transcription-PCR [RT-PCR] or real-time RT-PCR [rRT-PCR]), were developed and evaluated by various groups (7,13,15,16,26,30,34,35,46). The antigen detection immunoassay kits are designed to detect the NP of both influenza A and B viruses (7,40).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…PCR was also performed to detect the specific genes of equid herpesvirus (EHV) 1 and 4 in nasal swabs [12]. Rapid antigen detection kits were used to detect equine influenza virus in nasal swabs (Espline Influenza A&B-N, Fujirebio Inc., Tokyo, Japan) [22] and equine rotavirus in fecal samples (Dipstick "Eiken" Rota, Eiken Chemical Co., Ltd., Shimotsuga-gun, Japan) [15]. MLCB agar plates (Nissui Pharmaceutical Co., Ltd., Tokyo, Japan) were used to isolate Salmonella species from samples selectively enriched with Hajna tetrathionate broth (Eiken Chemical Co., Ltd.).…”
mentioning
confidence: 99%
“…The nasal swabs from these horses immersed in 2.5 ml of lactate broth medium containing 0.005% (w/v) gentamicin sulfate were tested by the rapid antigen detection (RAD) kit for influenza type A and B viruses (ESPLINE Flu A+B, Fujirebio, Japan) [11]. As a result, 12 samples showed positive results for influenza type A virus (Fig.…”
mentioning
confidence: 99%